Telemetry and genetics reveal asymmetric dispersal of a lake‐feeding salmonid between inflow and outflow spawning streams at a microgeographic scale. Issue 4 (7th February 2020) - Finlay, Ross; Poole, Russell; Coughlan, Jamie; Phillips, Karl P.; Prodöhl, Paulo; Cotter, Deirdre; McGinnity, Philip; Reed, Thomas E.
Abstract: The degree of natal philopatry relative to natal dispersal in animal populations has important demographic and genetic consequences and often varies substantially within species. In salmonid fishes, lakes have been shown to have a strong influence on dispersal and gene flow within catchments; for example, populations spawning in inflow streams are often reproductively isolated and genetically distinct from those spawning in relatively distant outflow streams. Less is known, however, regarding the level of philopatry and genetic differentiation occurring at microgeographic scales, for example, where inflow and outflow streams are separated by very small expanses of lake habitat. Here, we investigated the interplay between genetic differentiation and fine‐scale spawning movements of brown trout between their lake‐feeding habitat and two spawning streams (one inflow, one outflow, separated by <100 m of lake habitat). Most (69.2%) of the lake‐tagged trout subsequently detected during the spawning period were recorded in just one of the two streams, consistent with natal fidelity, while the remainder were detected in both streams, creating an opportunity for these individuals to spawn in both natal and non‐natal streams. The latter behavior was supported by genetic sibship analysis, which revealed several half‐sibling dyads containing one individual that was sampled as a fry in the outflow and another that was sampled as fry in the inflow. Genetic clustering analyses in conjunction with telemetry data suggested that asymmetrical dispersal patterns were occurring, with natal fidelity being more common among individuals originating from the outflow than the inflow stream. This was corroborated by Bayesian analysis of gene flow, which indicated significantly higher rates of gene flow from the inflow into the outflow than vice versa. Collectively, these results reveal how a combination of telemetry and genetics can identify distinct reproductive behaviors and associated asymmetries in natal dispersal that produce subtle, but nonetheless biologically relevant, population structuring at microgeographic scales. Abstract : We used a combination of PIT telemetry and genetic analyses to investigate the interplay between fine‐scale spawning movements and population structure of brown trout within a complex river system. Our research revealed evidence of distinctly asymmetrical, downstream‐biased dispersal patterns between inflow and outflow streams separated by less than 100 m of lake habitat. This asymmetry appears to facilitate the occurrence and maintenance of genetic structure at a microgeographic scale.